Contribution to the study of “Algorta” soils - Califra, A.; Ruiz, A.; Alliaume, F.; Durán, A. (Agrociencia Uruguay, 2007)
The Algorta mapping unit extends over than 135.000 ha in the Departments of Rio Negro and Paysandú (centralwestern Uruguay). Dominant soils are Argisoles and Planosoles Dístricos Ocricos, sandy family (Typic and Arenic Hapludalfs); associated soils are Brunosoles Subéutricos or Dístricos Típicos or Lúvicos (Abruptic Argiudolls) of the same textural family. Morphometric and analytical information is compiled and discussed en this paper and a data base is created, with the purpose of improving the knowledge about characterization and classification of these soils. The classification of some profiles included in the study is revised and they are now classified as Luvisoles (Arenic Hapludalfs). It is suggested to include them as accessory soils in the Algorta soil mapping unit. It is also proposed to define three soil Series: «Piedras Coloradas», with Planosoles Dístricos Ocricos, sandy family, hydromorphic phase; «Quebracho», with Argisoles Dístricos Ocricos or Melánicos, Albicos, Abrúpticos or Típicos, sandy family,; and «Menafra», with Luvisoles Ocricos (Albicos, Abrúpticos y Típicos), sandy family.